2014
DOI: 10.1186/2052-1847-6-23
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise modulates intracortical inhibition and facilitation in a nonexercised upper limb muscle

Abstract: BackgroundDespite growing interest in the relationship between exercise and short-term neural plasticity, the effects of exercise on motor cortical (M1) excitability are not well studied. Acute, lower-limb aerobic exercise may potentially modulate M1 excitability in working muscles, but the effects on muscles not involved in the exercise are unknown. Here we examined the excitability changes in an upper limb muscle representation following a single session of lower body aerobic exercise. Investigating the resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
188
7
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(218 citation statements)
references
References 72 publications
21
188
7
2
Order By: Relevance
“…Previous study reports increase in ICF following moderate intensity exercise [15]. The disparity between previous work and our study may be attributed to differences in exercise or TMS protocols (% AMT vs. % RMT).…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Previous study reports increase in ICF following moderate intensity exercise [15]. The disparity between previous work and our study may be attributed to differences in exercise or TMS protocols (% AMT vs. % RMT).…”
Section: Discussioncontrasting
confidence: 93%
“…Previous studies report reductions in SICI following moderate intensity exercise (~20% in [16] and ~35% in [15]). In our study, we observed an overall decrease of ~18%.…”
Section: Discussionmentioning
confidence: 99%
“…; Singh et al. ; Lulic et al. ), there are no reports of the effects of long‐term exercise interventions on corticospinal output and intracortical circuitry.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Singh et al. () have observed increased intracortical facilitation (ICF), while Lulic et al. () found decreased ICF in the M1 representations of upper limb muscles not involved in the exercise following a single biking session.…”
Section: Introductionmentioning
confidence: 99%
“…Also, M1 has shown to exhibit higher levels of activation during exercise (Christensen et al, 2000), and it is possible that this activation may help prime subsequent movements. An acute bout of lower extremity cycling exercise (20–30 min) at moderate and high intensity has been reported to reduce SICI in the M1 that lasts for up to 30 min after exercise (Singh, Duncan, Neva, & Staines, 2014; Smith, Goldsworthy, Garside, Wood, & Ridding, 2014). It is important to note that, in both these studies, the global effect of exercise was studied by examining M1 excitability of an unexercised upper limb muscle.…”
Section: Aerobic Exercise As Primingmentioning
confidence: 99%